Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Annetta_Martin

  • 3 years ago

Can someone help show me how they solve for 2(x – 4) – 12 = 2 – 3(x + 4) ?

  • This Question is Closed
  1. blue_sky1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    you have to use pemdas (2x-8) - 12 = -1x-4

  2. Annetta_Martin
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @CynthiaJune94

  3. electrokid
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    1. expand the paranthesis 2. rearrange to get all "x" terms on the left and all other terms to the right side of the "=" sign 3. simplify

  4. CynthiaJune94
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    2(x-4) -12 = 2 -3(x+4) 2x-8-12 = 2-3x-12 2x-20 = -3x-10 +20 +20 2x = -3x+10 +3x +3x 5x = 10 divide both sides by 5 x=2

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy